Magnetostrictive member and method for manufacturing the same

JP7643147B2Active Publication Date: 2025-03-11SUMITOMO METAL MINING CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2021064181
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-05
Publication Date
2025-03-11
Estimated Expiration
2041-04-05

AI Technical Summary

Benefits of technology

【0020】 本発明の態様によれば、磁歪部材の磁歪特特性、特に磁歪定数について、磁歪部材の表面が平坦で平滑な面に仕上げられた鏡面加工等に仕上げられた磁歪部材の磁歪定数と同等の特性を有し、かつ、磁歪部材の生産性を向上させることが出来る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643147000002
    Figure 0007643147000002
  • Figure 0007643147000003
    Figure 0007643147000003
  • Figure 0007643147000004
    Figure 0007643147000004
Patent Text Reader

Abstract

To obtain the magnetostrictive characteristics of a magnetostrictive member, especially the same characteristics as the magnetostrictive constant of the magnetostrictive member whose surface is finished to a flat and smooth surface such as a mirror finish, and improve the productivity of the magnetostrictive member.SOLUTION: A magnetostrictive member is made of iron-based alloy crystals having magnetostrictive characteristic, and has a surface roughness Ra of 2.4 μm or less on at least one surface.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a magnetostrictive member and a method for manufacturing a magnetostrictive member. [Background technology]

[0002] Magnetostrictive materials have been attracting attention as functional materials. For example, Fe-Ga alloys, which are iron-based alloys, are materials that exhibit magnetostrictive and inverse magnetostrictive effects, and exhibit large magnetostriction of about 100 to 350 ppm. Therefore, in recent years, they have been attracting attention as vibration power generation materials in the energy harvesting field, and are expected to be applied to wearable terminals and sensors. As a method for producing single crystals, a method for growing single crystals by a pulling method (Czochralski method, hereinafter abbreviated as "Cz method") is known (for example, Patent Document 1). In addition to the Cz method, the vertical Bridgman method (VB method) and the vertical temperature gradient solidification method (VGF method) are known as production methods (for example, Patent Document 2 and Patent Document 3).

[0003] Magnetostriction properties depend on the crystal orientation. In Fe-Ga alloys, the crystal orientation <100> The magnetostrictive material has an easy axis of magnetization in the direction of the magnetization, and can exhibit large magnetostriction in this direction. Conventionally, magnetostrictive materials made of Fe-Ga alloys are made of polycrystalline Fe-Ga alloys. <100> Magnetostrictive magnets are manufactured by cutting a single crystal part oriented in a certain direction to the desired size (for example, non-patent document 1). However, since the crystal orientation greatly affects the magnetostrictive properties, the direction in which magnetostriction of the magnetostrictive member is required and the direction in which the magnetostriction of the crystal is maximum must be considered. <100> It is believed that a single crystal with the same orientation is the most suitable material for the magnetostrictive member.

[0004] The Fe-Ga alloy single crystal is <100> When a magnetic field is applied parallel to the direction, positive magnetostriction appears (hereinafter referred to as "parallel magnetostriction"). <100> When a magnetic field is applied perpendicular to the orientation, negative magnetostriction appears (hereinafter referred to as "perpendicular magnetostriction"). When the strength of the applied magnetic field is gradually increased, the parallel magnetostriction or perpendicular magnetostriction is saturated. The magnetostriction constant (3 / 2λ 100) is determined by the difference between the saturated parallel magnetostriction amount and the saturated perpendicular magnetostriction amount, and is calculated by the following formula (1) (for example, Patent Document 4 and Non-Patent Document 2).

[0005] 3 / 2λ 100 =ε( / / )― ε(⊥) ···Equation (1) 3 / 2λ 100 :Magnetostriction constant ε( / / ): <100> Parallel magnetostriction when saturated by applying a magnetic field parallel to the direction ε(⊥): <100> The amount of perpendicular magnetostriction when a magnetic field is applied perpendicular to the direction and saturated

[0006] Magnetostrictive properties depend on the composition of the magnetostrictive material. The magnetostrictive properties of Fe-Ga alloys are considered to affect the magnetostrictive and inverse magnetostrictive effects and the properties of magnetostrictive vibration power generation devices, and are an important parameter in device design (e.g., Non-Patent Document 4). In particular, it is known that the magnetostrictive constant depends on the Ga composition of Fe-Ga alloy single crystals, and the magnetostrictive constant is maximized when the Ga composition is 18-19 at% and 27-28 at% (e.g., Non-Patent Document 2), and it is considered desirable to use Fe-Ga alloys with such Ga concentrations in devices.

[0007] A magnetostrictive vibration power generation device is composed of, for example, an Fe-Ga magnetostrictive member wound around a coil, a yoke, and a permanent magnet for a field magnet (for example, Patent Document 5 and Non-Patent Document 3). In this magnetostrictive vibration power generation device, when the yoke of the movable part of the device is vibrated, the Fe-Ga magnetostrictive member fixed to the center of the yoke vibrates in conjunction with it, and the inverse magnetostrictive effect changes the magnetic flux density of the coil wound around the Fe-Ga magnetostrictive member, generating an electromagnetically induced electromotive force and generating electricity. In a magnetostrictive vibration power generation device, a force is applied in the longitudinal direction of the yoke to cause vibration, so the Fe-Ga magnetostrictive member used in the device is arranged along the easy axis of magnetization. <100> It is preferable to process the wire so that the length direction is the longitudinal direction.

[0008] Magnetostrictive elements that utilize the magnetostrictive phenomenon are susceptible to the magnetic and magnetostrictive properties due to the magnetoelastic energy effect caused by mechanical strain, the so-called inverse magnetostrictive effect. Therefore, it is desirable to avoid unintended stress or local strain when applying the element. For example, processing strain may cause a decrease in magnetostrictive properties, a decrease in the strength of the element, deterioration of fatigue properties, and a decrease in yield due to characteristic variations (Patent Document 6). Regarding the evaluation of the magnetostrictive properties of FeGa(Al)-based alloy materials, examples have been reported in which the alloy sample surface is polished with SiC polishing paper to remove the processing-strained surface and adjust the shape (Patent Document 7, Non-Patent Documents 4 and 5).

[0009] In addition, since magnetostrictive elements are elements that utilize the coupling and conversion between magnetic elements and mechanical elements, the mechanical shape is important. Therefore, it is desirable for the surface of the magnetostrictive material to be flat or a smooth curved surface with few irregularities (Patent Document 7). [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2016-28831 A [Patent Document 2] JP 2016-138028 A [Patent Document 3] Japanese Patent Application Publication No. 4-108699 [Patent Document 4] Special Publication No. 2015-517024 [Patent Document 5] International Publication No. 2011-158473 [Patent Document 6] JP 2006-253614 A [Patent Document 7] Patent No. 4895108 [Non-patent literature]

[0011] [Non-Patent Document 1] Etrema, State of the Art of Galfenol Processing. [Non-Patent Document 2] AE Clark et al., Appl. Phys. 93(2003)8621. [Non-Patent Document 3] Toshiyuki Ueno, Journal of the Japan Society for Precision Engineering, Vol. 79, No.4, (2013) 305-308. [Non-Patent Document 4] S. Asano et al., IEEE Magnetics Letters, Volume 8(2017)6101004. [Non-Patent Document 5] C. Mudivarthi et al, J. Appl. Phys., vol.322 (2010)2023-2026. Summary of the Invention [Problem to be solved by the invention]

[0012] Since the device characteristics of magnetostrictive vibration power generation devices and the like are affected by the magnetostrictive properties of the magnetostrictive member, the magnetostrictive member is required to have high magnetostrictive properties and little variation in the magnetostrictive properties. In this situation, if the magnetostrictive member is a single crystal and has a uniform crystal composition, the magnetostriction constant will be uniform.

[0013] As mentioned above, when the surface of a magnetostrictive member is subjected to mechanical strain, the magnetic properties and magnetostrictive properties, especially the magnetostriction constant, are affected. Therefore, the surface of the magnetostrictive member is finished to a flat and smooth surface by mirror finishing or the like to prevent unintended stress or local strain.

[0014] However, mirror finishing of the surface of the magnetostrictive member requires a long time of processing with an abrasive material, which reduces productivity.

[0015] In view of the above circumstances, the present invention aims to provide a magnetostrictive member and a method for manufacturing a magnetostrictive member, which has magnetostrictive characteristics, particularly the magnetostriction constant, equivalent to the magnetostriction constant of a magnetostrictive member whose surface has been finished by mirror finishing or the like to a flat and smooth surface, and which improves the productivity of the magnetostrictive member. [Means for solving the problem]

[0016] According to an aspect of the present invention, there is provided a magnetostrictive member made of crystals of an iron-based alloy having magnetostrictive properties, the magnetostrictive member having at least one surface with a surface roughness Ra of 2.4 μm or less.

[0017] The magnetostrictive member according to the embodiment of the present invention may be plate-shaped and have a surface roughness Ra of 2.4 μm or less on the front and back surfaces. The surface having a surface roughness Ra of 2.4 μm or less may be a ground surface. The magnetostrictive constant may be 80% or more of the magnetostrictive constant when the front and back surfaces of the magnetostrictive member are polished surfaces.

[0018] According to another aspect of the present invention, there is provided a method for manufacturing a magnetostrictive member made of iron-based alloy crystals having magnetostrictive properties, the method including surface-processing at least one surface to a surface roughness Ra of 2.4 μm or less.

[0019] In the manufacturing method of the magnetostrictive member according to the aspect of the present invention, the surface treatment may be a grinding process using a grindstone having a grit size of #100 or more and #1000 or less. Effect of the Invention

[0020] According to an embodiment of the present invention, the magnetostrictive characteristics, particularly the magnetostrictive constant, of the magnetostrictive member have characteristics equivalent to the magnetostrictive constant of a magnetostrictive member whose surface has been finished into a flat and smooth surface, such as a mirror finish, and the productivity of the magnetostrictive member can be improved. [Brief description of the drawings]

[0021] [Figure 1] FIG. 2 is a diagram showing an example of a magnetostrictive member according to an embodiment. [Diagram 2] 3 is a flowchart showing an example of a method for manufacturing a magnetostrictive member according to the embodiment. [Diagram 3] 1A to 1C are diagrams showing a first example of a single crystal, a thin plate member, and a magnetostrictive member. [Figure 4] 1A to 1C are diagrams showing a second example of a single crystal, a thin plate member, and a magnetostrictive member. [Diagram 5] 11A and 11B are diagrams showing a third example of a single crystal, a thin plate member, and a magnetostrictive member. [Figure 6] FIG. 1 is a diagram showing the strain gauge method used in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Specific embodiments of the present invention will be described in detail below. The present invention is not limited to the following embodiments, and can be modified as appropriate without departing from the gist of the present invention. In each drawing, a part or whole is depicted diagrammatically as appropriate, and the scale is changed. In the following description, the expression "A to B" means "A or more and B or less."

[0023] FIG. 1 is a diagram showing an example of a magnetostrictive member according to this embodiment. The magnetostrictive member 1 is made of crystals of an iron-based alloy. The iron-based alloy is not particularly limited as long as it has magnetostrictive properties. The magnetostrictive properties refer to a property in which a change in shape occurs when a magnetic field is applied. The iron-based alloy is, for example, an alloy such as Fe-Ga, Fe-Ni, Fe-Al, Fe-Co, Tb-Fe, Tb-Dy-Fe, Sm-Fe, or Pd-Fe. The above alloy may also be an alloy to which a third component is added. For example, an Fe-Ga alloy may be an alloy to which Ba, Cu, or the like is added. Among these iron-based alloys, the Fe-Ga alloy has a large magnetostrictive property and is easy to process compared to other alloys, and is therefore applied to vibration power generation materials in the energy harvesting field, wearable terminals, sensors, and the like. The crystal that can be used for the magnetostrictive member 1 of this embodiment may be a single crystal or a polycrystal. <100> In order to increase the degree of orientation integration in the direction and improve the properties of the magnetostrictive material, it is more advantageous to use a single crystal than a polycrystal. Although the magnetostrictive properties of a polycrystal are inferior to those of a single crystal, polycrystals can be produced at low cost, so they may be used. In the following explanation, as an example of the magnetostrictive member 1, an example of a configuration in which the magnetostrictive member 1 is made of a single crystal of an Fe-Ga alloy will be explained.

[0024] The single crystal of the Fe-Ga alloy has a body-centered cubic lattice structure, and the first to third directional indices in the Miller indices <100> The basis of this is that the axes (see Figs. 3 to 5) are equivalent, and the first to third {100} planes (see Figs. 3 to 5) among the plane indices in the Miller indices are equivalent (i.e., (100), (010) and (001) are equivalent). Furthermore, Fe-Ga alloys have the property of producing large magnetostriction in a specific orientation of the crystal. When this property is utilized in a magnetostrictive vibration power generation device, it is desirable to match the direction in the device where magnetostriction of the magnetostrictive member 1 is required with the orientation (direction) where the magnetostriction of the crystal is maximum. Specifically, as described above, the direction of easy magnetization in a single crystal is <100> It is desirable to set the direction of magnetization in the longitudinal direction of the magnetostrictive member 1. <100> The direction can be set to the longitudinal direction of the magnetostrictive member 1, for example, by calculating the crystal orientation of the single crystal by known crystal orientation analysis and cutting the single crystal based on the calculated crystal orientation of the single crystal.

[0025] The magnetostrictive member 1 is used, for example, as a material (part) for vibration power generation devices in the energy harvesting field, and as a material (part) for wearable terminals and sensors. For example, a magnetostrictive vibration power generation device as shown in the above-mentioned Patent Document 5 is composed of a coil, a magnetostrictive member made of an Fe-Ga alloy wound around the coil, a yoke, and a permanent magnet for a field magnet. This magnetostrictive vibration power generation device has a mechanism in which, when a yoke, which is a movable part of the device, is vibrated, the magnetostrictive member fixed to the center of the yoke vibrates in conjunction with the yoke, and the magnetic flux density of the coil wound around the magnetostrictive member changes due to the inverse magnetostrictive effect, and an electromagnetically induced electromotive force is generated, thereby generating electricity. When used in such a mechanism, the shape of the magnetostrictive member 1 is preferably a thin plate shape and is set to a long and narrow rectangular shape in a plan view. For example, the magnetostrictive member 1 may have a shape as shown in FIG. 1. The magnetostrictive member 1 shown in FIG. 1 is a plate-like body having a rectangular shape in a plan view, and has a front surface (front surface) 3, a back surface 4, and side surfaces 5 and 6. The front surface 3 and the back surface 4 are preferably parallel to each other, but may not be parallel to each other.

[0026] The thickness of the magnetostrictive member 1 is not particularly limited. The lower limit of the thickness is preferably 0.3 mm or more, more preferably 0.5 mm or more. The upper limit of the thickness of the magnetostrictive member 1 is preferably 1.5 mm or less. The thickness of the magnetostrictive member 1 is preferably 0.3 mm or more and 1.5 mm or less, more preferably 0.5 mm or more and 1.0 mm or less. As described above, the mechanism of power generation by the magnetostrictive member 1 is a mechanism of generating power by applying stress (vibration) to the magnetostrictive member through the inverse magnetostrictive effect. If the thickness of the magnetostrictive member 1 is less than 0.3 mm, it is easily damaged during vibration. On the other hand, if the thickness of the magnetostrictive member 1 exceeds 1.5 mm, it is necessary to increase the stress due to vibration, and the efficiency is reduced. The shape and size of the magnetostrictive member 1 are appropriately set according to the size of the target device. For example, the size of the magnetostrictive member 1 is the size shown in Examples 1 to 6.

[0027] The shape and dimensions of the magnetostrictive member 1 are not particularly limited. For example, the magnetostrictive member 1 does not have to be rectangular in plan view. For example, the shape of the magnetostrictive member 1 may be elliptical, track-like, or irregular in plan view. When the shape of the magnetostrictive member 1 is other than rectangular in plan view, the longitudinal direction is the major axis direction, the major axis direction, etc., and the lateral direction is the direction perpendicular to the longitudinal direction.

[0028] The present inventors have developed a single crystal of an Fe-Ga alloy, the principal surface of which is the {100} plane and the magnetization direction is the easy direction. <100> A plurality of plate-shaped magnetostrictive members were produced, each having a rectangular shape in plan view with the direction of the magnetostrictive member being the longitudinal direction. As a result of confirming the magnetostrictive properties (magnetostriction constant) of a plurality of magnetostrictive members cut out from a single crystal of an Fe-Ga alloy with a uniform Ga concentration, it was confirmed that the measured value of the magnetostrictive constant varies depending on the finishing state of the front and back surfaces of the magnetostrictive member. In general, when the surface of a magnetostrictive member is subjected to mechanical strain, the magnetic properties and magnetostrictive properties, especially the magnetostrictive constant, are affected. Therefore, it is preferable to finish the surface of the magnetostrictive member into a flat and smooth surface by mirror finishing or the like so that there is no unintended stress or local distortion. However, in order to mirror finish the surface of the magnetostrictive member, it is necessary to process it with an abrasive for a long time, which causes a problem of reduced productivity. As a result of further investigation, the present inventors found that there is a relationship between the magnetostrictive constant and the surface state of the magnetostrictive member. The present invention was made based on the above findings.

[0029] The magnetostrictive member 1 of this embodiment is characterized in that at least one surface has a surface roughness Ra of 2.4 μm or less, as will be described in detail below.

[0030] The magnetostrictive characteristics of the magnetostrictive member 1 of this embodiment are evaluated by the magnetostriction constant. As described above, the magnetostriction constant (3 / 2λ 100 ) is calculated as the difference between the saturated parallel magnetostriction and the saturated perpendicular magnetostriction. <100> When a magnetic field is applied parallel to the direction, the value at which positive magnetostriction appears and saturates is defined as the amount of parallel magnetostriction. <100> When a magnetic field is applied perpendicular to the orientation, the value at which negative magnetostriction appears and saturates is defined as the perpendicular magnetostriction. These magnetostriction amounts are evaluated using the strain gauge method. Note that when using a single crystal magnetostrictive material with a non-uniform composition, the magnetostriction constant changes. Therefore, it is important to prepare a single crystal magnetostrictive material with a uniform composition. Details of the method for measuring the magnetostriction constant will be described later.

[0031] The properties of a magnetostrictive member, particularly the magnetostriction constant, are related to the surface condition of the magnetostrictive member. If processing distortion remains on the surface of the magnetostrictive member, the processing distortion may cause the magnetic domain direction of the magnetostrictive member to change, making it impossible to obtain the desired magnetostriction constant. For this reason, it is considered preferable to finish the surface of the magnetostrictive member to a flat and smooth surface by mirror finishing or the like to prevent unintended stress or local distortion.

[0032] Therefore, in the present invention, as shown in the examples, tests were carried out on the relationship between the surface condition (surface roughness) of the magnetostrictive member and the magnetostriction constant.

[0033] In the embodiment, a magnetostrictive member is obtained by obtaining an Fe-Ga alloy single crystal, cutting the Fe-Ga alloy single crystal with a uniform concentration so that the gallium content is 18 to 19 at.% by atomic weight as determined by ICP analysis, and processing the surface to a specified surface roughness.

[0034] As shown in the reference example, the magnetostrictive member whose front and back surfaces were mirror-finished had a magnetostriction constant of 300 ppm.

[0035] In contrast, as shown in Examples 1 to 6, by performing processing with a wire saw or surface grinding processing with a surface grinder on the surface of the magnetostrictive member and setting the surface roughness Ra of at least one surface (one side) of the front and back sides to 2.4 μm or less, it is possible to maintain the magnetostrictive constant equivalent to that of a magnetostrictive member having mirror-finished front and back sides. As shown in Examples 1 to 6, a magnetostrictive constant of 80% or more can be obtained compared to the magnetostrictive constant of a magnetostrictive member having mirror-finished front and back sides. The smaller the surface roughness Ra, the higher the magnetostrictive constant can be. For example, by setting the surface roughness Ra to 1.0 μm or less, a magnetostrictive constant of more than 95% can be obtained compared to the magnetostrictive member having mirror-finished front and back sides.

[0036] When the surface roughness is ground using a surface grinder or the like, the surface roughness Ra in the vertical direction perpendicular to the grinding direction (hereinafter sometimes simply referred to as the vertical direction) becomes large. Therefore, the value of the surface roughness Ra is the value in the direction in which the surface roughness is maximum when measured in two directions, the grinding direction and the direction perpendicular to the grinding direction. Similarly, the surface roughness Ra in the magnetostrictive member 1 of this embodiment and the manufacturing method of the magnetostrictive member of this embodiment described later is the value in the direction in which the surface roughness is maximum within one surface.

[0037] In addition, the magnetostriction constant (3 / 2λ 100 Since the difference between the saturated parallel magnetostriction amount and the saturated perpendicular magnetostriction amount is determined by the difference between the saturated parallel magnetostriction amount and the saturated perpendicular magnetostriction amount, no difference occurs depending on the grinding direction. Note that in the magnetostrictive member 1 of this embodiment and the manufacturing method of the magnetostrictive member of this embodiment described later, the measurement direction of the parallel magnetostriction amount is the grinding direction.

[0038] The surface of the magnetostrictive member having a surface roughness Ra of 2.4 μm or less may be at least one of the front and back surfaces of the magnetostrictive member, but may be both of the front and back surfaces. In addition, the surface shape of the surface having a surface roughness Ra of 2.4 μm or less in the magnetostrictive member 1 is not particularly limited. For example, the surface having a surface roughness Ra of 2.4 μm or less is preferably a ground surface. When the surface having a surface roughness Ra of 2.4 μm or less is a ground surface, the processing speed is high, and therefore the productivity is high. When the surface having a surface roughness Ra of 2.4 μm or less is a ground surface, the direction in which the grinding process is performed in the magnetostrictive member 1 is not particularly limited, but is preferably a direction along the longitudinal direction of the magnetostrictive member 1. Here, the direction along the longitudinal direction includes a direction intersecting the longitudinal direction at an angle of 40° or less. In addition, the lower limit of the surface roughness Ra of the surface having a surface roughness Ra of 2.4 μm or less is not particularly limited as long as Ra is larger than that of a mirror surface, but is preferably 0.03 μm or more.

[0039] As described above, the magnetostrictive member 1 of this embodiment is a magnetostrictive member made of crystals of an iron-based alloy having magnetostrictive properties, and at least one surface has a surface roughness Ra of 2.4 μm or less. That is, the magnetostrictive member 1 of this embodiment has a surface with a surface roughness Ra of 2.4 μm or less, preferably 2.0 μm or less, more preferably 1.5 μm or less, more preferably 1.0 μm or less, and more preferably 0.8 μm or less. In the magnetostrictive member 1 of this embodiment, the configuration other than the above is optional. The magnetostrictive member 1 of this embodiment has the same magnetostrictive characteristics, particularly the magnetostriction constant, as the magnetostrictive constant of a magnetostrictive member whose surface is finished by mirror finishing or the like to be flat and smooth, and can improve the productivity of the magnetostrictive member. For example, the magnetostrictive member 1 of this embodiment has a magnetostriction constant of 250 ppm or more, more preferably 280 ppm or more, and even more preferably 290 ppm or more. Furthermore, the magnetostrictive member 1 of this embodiment has a magnetostrictive constant characteristic that is 80% or more, preferably 90% or more, and more preferably 95% or more of the magnetostrictive constant of a magnetostrictive member having mirror-finished front and back surfaces. Since the magnetostrictive member 1 of this embodiment has a high magnetostrictive constant as described above, it can be suitably used as a final product of a member (material) that exhibits excellent magnetostrictive effect and inverse magnetostrictive effect.

[0040] Next, a method for producing the magnetostrictive member of the present invention will be described.

[0041] The manufacturing method of the magnetostrictive member of this embodiment is the manufacturing method of the magnetostrictive member 1 of this embodiment described above. The manufacturing method of the magnetostrictive member of this embodiment includes surface processing of the front and back surfaces of the magnetostrictive member made of crystals of an iron-based alloy having magnetostrictive properties to a surface roughness of Ra 2.4 μm or less. In the following description, a method of manufacturing the magnetostrictive member 1 from a single crystal ingot of an Fe-Ga alloy is described as an example, but the manufacturing method of the magnetostrictive member of this embodiment is not limited to the following description. In addition, among the descriptions in this specification, those that are applicable to the manufacturing method of the magnetostrictive member of this embodiment are also applicable to the manufacturing method of the magnetostrictive member of this embodiment. In addition, among the descriptions of the manufacturing method of the magnetostrictive member of this embodiment, those that are applicable to the magnetostrictive member of this embodiment are also applicable to the magnetostrictive member of this embodiment. In addition, the manufacturing method of the magnetostrictive member 1 of this embodiment is not limited to the manufacturing method of the magnetostrictive member of this embodiment described below, and may be manufactured by other manufacturing methods.

[0042] Fig. 2 is a flow chart showing an example of a manufacturing method for a magnetostrictive member of this embodiment. Fig. 3 to Fig. 5 are diagrams showing first to third examples of a single crystal, a thin plate member, and a magnetostrictive member. The manufacturing method for the magnetostrictive member of this embodiment includes a crystal preparation step (step S1), a crystal cutting step (step S2), a surface processing step (step S3), and a cutting step (step S4).

[0043] In the manufacturing method of the magnetostrictive member of this embodiment, first, in a crystal preparation step (step S1), a crystal of an iron-based alloy having magnetostrictive properties is prepared. The prepared crystal may be a single crystal or a polycrystal. The prepared crystal may be a grown crystal or a commercially available product. For example, in the crystal preparation step, a single crystal of an Fe-Ga alloy is prepared. There is no particular limitation on the method for growing the single crystal of an Fe-Ga alloy. The method for growing the single crystal of an Fe-Ga alloy may be, for example, a pulling method or a unidirectional solidification method. For example, the Cz method may be used as the pulling method, and the VB method, VGF method, and micro-pulling down method may be used as the unidirectional solidification method.

[0044] Although single crystals can be obtained by the Cz method, there is a problem that the composition varies widely. Therefore, it is more preferable to use single crystals grown by the VB method, which can obtain high-quality single crystals like the Cz method and has a high composition uniformity.

[0045] The Fe-Ga alloy single crystal has a maximum magnetostriction constant when the gallium content is 18.5 at% or 27.5 at%. For this reason, the Fe-Ga alloy single crystal is preferably grown to have a gallium content of 16.0 to 20.0 at% or 25.0 to 29.0 at%, and more preferably grown to have a gallium content of 17.0 to 19 at% or 26.0 to 28.0 at%. The shape of the grown single crystal is not particularly limited, and may be, for example, cylindrical or rectangular prism. The grown single crystal may be cut into a cylindrical single crystal by cutting the seed crystal, the diameter-increasing portion or the shoulder portion (the portion that increases the diameter from the seed crystal to a predetermined single crystal diameter) with a cutting device as necessary. The size of the grown single crystal is not particularly limited as long as the magnetostrictive member can be secured in a predetermined direction. When growing an Fe-Ga alloy single crystal, the growth axis direction is <100> The seed crystal is grown using a seed crystal whose upper or lower surface is processed to have a {100} plane so that the Fe-Ga alloy single crystal is grown in a direction perpendicular to the upper or lower surface of the seed crystal, and inherits the orientation of the seed crystal.

[0046] Following the crystal preparation step (step S1), a crystal cutting step (step S2) is carried out. The crystal cutting step is a step of cutting a crystal to create a thin plate member. The thin plate member is a member that will be the material of the magnetostrictive member 1 of this embodiment. The crystal cutting step is, for example, a step of cutting a single crystal of an Fe-Ga alloy having magnetostrictive properties using a cutting device to create a thin plate member having a {100} plane as the main surface. The cutting device may be a wire electric discharge machine, an inner diameter blade cutting device, a wire saw, or other cutting device. Among them, it is particularly preferable to use a multi-wire saw, since it is possible to cut multiple thin plate members at the same time. In the case of a single crystal of an Fe-Ga alloy, the cutting direction of the single crystal is as follows: <100> The cutting surface, i.e., the main surface of the thin plate member, is cut so as to be a {100} plane. The cutting direction of the single crystal is not particularly limited. For example, as shown in Figures 3 to 5, the cutting direction of the single crystal may be perpendicular or parallel to the growth direction of the single crystal (the direction in which the crystal is grown).

[0047] Following the crystal cutting step (step S2), a surface processing step (step S3) is carried out. In the surface processing step, at least one of the front surface 3 and back surface 4 of the obtained thin plate member is surface-processed so that the surface roughness Ra is 2.4 μm or less (hereinafter, also referred to as the predetermined surface roughness). In the surface processing step, the thin plate member is surface-processed so that when the thin plate member is finally cut into the magnetostrictive member 1, the magnetostrictive member 1 will have a surface roughness Ra of 2.4 μm or less. As described above, the predetermined surface roughness Ra can be obtained by performing surface processing on at least one of the front and back surfaces of the thin plate member obtained by the crystal cutting step.

[0048] The surface processing is not particularly limited as long as it can be processed to a predetermined surface roughness Ra. For example, it may be a grinding process using a grinding wheel on a surface grinder, or a grinding process using a slurry containing abrasive grains on a double-sided lapping device. It may also be a grinding process using a wire saw. Furthermore, although it is not a grinding process, it may be a process such as electric discharge machining that can achieve a predetermined surface roughness Ra by adjusting the machining conditions with a wire electric discharge machine.

[0049] An example in which the surface processing step is performed by surface grinding of a thin plate member will be described below.

[0050] Surface grinding is performed using a surface grinder. The surface grinder can be one in which the grinding wheel or processing table moves in a linear direction and the processing table moves back and forth using a flat grinding wheel. It is also possible to use a surface grinder in which the processing table rotates using a cup grinding wheel.

[0051] In the surface processing step, the surface of the thin plate member (magnetostrictive member) may be polished to a mirror finish as in the conventional method, and then the surface may be ground, but this is not preferable from the viewpoint of the productivity of the magnetostrictive member. It is preferable to perform the surface processing (grinding) on ​​both the front and back surfaces of the thin plate member.

[0052] The grindstone used for surface grinding is selected so as to have a predetermined surface roughness. For example, the lower limit of the roughness (grit) of the grindstone is preferably #100 or more, more preferably #200 or more. The upper limit of the roughness (grit) of the grindstone is not particularly limited, but from the viewpoint of the productivity of the magnetostrictive member, it is preferably #1000 or less, more preferably #600 or less, and the range is preferably #100 or more and #1000 or less, more preferably #200 or more and #600 or less. When the roughness (grit) of the grindstone is within the above range, the magnetostrictive constant can be 80% or more, preferably 85% or more, more preferably 90% or more, and even more preferably 95% or more of the magnetostrictive constant at the time of mirror finishing. Note that if a grindstone smaller than #100 is used, processing distortion may remain in the magnetostrictive member, which may reduce the magnetostrictive constant. If a grindstone exceeding #1000 is used, the grindstone may become clogged during processing, resulting in reduced productivity.

[0053] The surface processing step may be a grinding process using a wire saw. When cutting with a wire saw, the crystal cutting step (step S2) and the surface processing step (step S3) can be shared, and a thin plate member can be efficiently manufactured. In surface processing using a wire saw, there are a free abrasive method in which the workpiece is pressed against a row of parallel ultra-fine wires at a constant pitch, and a processing liquid (also called a slurry) containing abrasive grains is supplied between the workpiece and the wire while the wire is fed in the linear direction to cut the workpiece, and a fixed abrasive method in which a wire with abrasive grains such as diamond fixed by electroplating or adhesive is fed in the linear direction to cut the workpiece. Both methods can be used in this embodiment. The abrasive grains used in the wire saw are selected so as to have a predetermined surface roughness. For example, SiC, #1000 abrasive grains can be used.

[0054] Furthermore, instead of grinding, electric discharge machining may be used to obtain a predetermined surface roughness Ra. For example, the above-mentioned predetermined surface roughness may be obtained by adjusting the machining conditions using a wire electric discharge machine.

[0055] In the surface processing step of the magnetostrictive member, grinding, which has a high processing speed, is more preferable from the viewpoint of processing speed. For example, the grinding is preferably grinding by a wire saw or surface grinding.

[0056] Following the surface processing step (step S3), a cutting step (step S4) is carried out. The cutting step is a step of cutting the thin plate member that has been given a predetermined surface roughness Ra by the surface processing step, to obtain the magnetostrictive member 1 of this embodiment.

[0057] In the cutting process, the thin plate member is cut to a predetermined size. In the cutting process, the thin plate member is cut as the magnetostrictive member 1 so that the magnetostrictive member 1 becomes a rectangular plate-like body in a plan view. In the cutting process, the thin plate member is cut using a cutting device. The cutting device used in the cutting process is not particularly limited, and for example, a peripheral blade cutting device, a wire electric discharge machine, a wire saw, etc. can be used. There is no particular limit to the direction in which the magnetostrictive member is extracted from the thin plate member, and for example, it may be set to a direction in which the magnetostrictive member can be efficiently obtained based on the size of the magnetostrictive member. In addition, the magnetostriction constant of the magnetostrictive member 1 depends on the state of the front and back surfaces of the magnetostrictive member, and is not affected by the surface state of the side surface. Therefore, in manufacturing the magnetostrictive member 1, the processing method of the side surface of the magnetostrictive member 1 is not particularly limited.

[0058] As described above, the method for manufacturing a magnetostrictive member according to this embodiment is a method for manufacturing a magnetostrictive member made of crystals of an iron-based alloy having magnetostrictive properties, and includes surface processing of at least one surface to a surface roughness Ra of 2.4 μm or less. Note that in the method for manufacturing a magnetostrictive member according to this embodiment, configurations other than those described above are optional. According to the method for manufacturing a magnetostrictive member according to this embodiment, the magnetostrictive member 1 of the above embodiment can be manufactured, thereby improving the productivity of magnetostrictive members. EXAMPLES

[0059] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples in any way.

[0060] [Example 1] The raw materials were adjusted to a stoichiometric ratio of iron and gallium of 81:19, and a cylindrical Fe-Ga alloy single crystal with a diameter of 52 mm and a straight body length of 100 mm was prepared by growing using the vertical Bridgman (VB) method. The growth axis direction of the single crystal is <100> The orientation of the {100} plane on the top or bottom surface of the single crystal perpendicular to the crystal growth axis direction was confirmed by X-ray diffraction. At this time, the crystal composition was measured every 10 mm using a Shimadzu sequential plasma emission spectrometer (ICPS-8100), and the gallium content in the region 10 to 70 mm from the start of the straight body was found to be 18.0 to 19.0 at%. A peripheral blade cutter was used to cut off the region other than the region 10 to 70 mm from the start of the straight body.

[0061] A magnetostrictive member was manufactured from the grown single crystal as follows. First, a wire saw with a loose abrasive grain type wire saw was used to cut the single crystal in a direction parallel to the growth direction ( <100> The single crystal was cut in a direction parallel to the {100} crystal orientation to produce thin plate members with cut surfaces, i.e., the main surfaces, of {100}. The cutting pitch was 1.2 mm, and the cutting thickness was 1 mm.

[0062] Next, two thin plate members were selected that were cut to approximately 50 x 60 mm near the center of the crystal. Next, the two thin plate members, approximately 50 x 60 mm near the center of the crystal, were cut into 10 mm x 10 mm x 1 mm (length x width x thickness) using a dicing device to produce 50 wire saw finished members.

[0063] Ten pieces were selected from the wire saw finished parts, and the surface roughness Ra was measured at five points in two directions, the wire running direction of the wire saw device and the direction perpendicular to the wire running direction, with a surface roughness meter (manufactured by Keyence Corporation) at a magnification of 20 times. The average values ​​were taken as the surface roughness in each direction, and the value in the direction with the maximum value was taken as the surface roughness Ra of the part. Ten pieces were measured, and the maximum and minimum values ​​were taken. The surface roughness Ra was 0.5 to 0.6 μm. In the following description, when the measured surface roughness Ra is A or B, it is expressed as A to B.

[0064] Next, the magnetostriction constant was measured. A strain gauge (manufactured by Kyowa Electric Industry Co., Ltd.) was attached to the member with an adhesive. The longitudinal direction of the strain gauge was aligned with the magnetostrictive member. <100> The wire was attached so that it was parallel to the direction of the grinding wire and the measurement direction of the parallel magnetostriction was the running direction of the wire (grinding direction).

[0065] The magnetostriction measuring device is composed of a neodymium magnet, a bridge box, a compact recording system, a strain unit, and dynamic data acquisition software. The actual measurement is performed at room temperature of 25°C and in a magnetic field of 0.2 T, and the amount of magnetostriction is determined by correcting it with the gauge factor. The correction of the gauge factor is made using the following formula (2).

[0066] ε=2.00 / Ks × εi...Equation (2) (ε: gauge factor, εi: measured strain value, Ks: gauge factor of the gauge used)

[0067] The magnetostriction constant is determined according to formula (1). When the magnetostriction constant of 10 wire saw finished parts was measured, the average value was 303 ppm, which was equivalent to the average value of 300 ppm for the magnetostriction constant of 10 mirror polished parts machined from the same area. The manufacturing conditions and evaluation results are shown in Table 1.

[0068] [Example 2] A #400 grindstone was set on a surface grinder, and 10 wire saw finished members used in Example 1 were ground by 100 μm on each side to produce #400 ground finished members measuring 10 mm × 10 mm × 0.8 mm (length × width × thickness). The surface roughness of this was measured. The surface roughness Ra was 0.2 to 0.4 μm.

[0069] When the magnetostriction constant of 10 pieces with a #400 grinding finish was measured, the average value was 303 ppm, which was equivalent to the average value of 300 ppm for the magnetostriction constant of 10 pieces with a mirror polishing finish machined from the same area. The manufacturing conditions and evaluation results are shown in Table 1.

[0070] [Example 3] A #600 grindstone was set on a surface grinder, and 10 #400 finished parts used in Example 2 were ground by 100 μm on each side to produce #600 ground finished parts measuring 10 mm × 10 mm × 0.6 mm (length × width × thickness). The surface roughness of this was measured. The surface roughness Ra was 0.1 to 0.2 μm.

[0071] When the magnetostriction constant of 10 pieces with a #600 grinding finish was measured, the average value was 302 ppm, which was equivalent to the average value of 300 ppm for the magnetostriction constant of 10 pieces with a mirror polishing finish machined from the same area. The manufacturing conditions and evaluation results are shown in Table 1.

[0072] [Example 4] A #1000 grindstone was set on a surface grinder, and ten #600 finished members used in Example 3 were ground by 20 μm on each side to produce #1000 ground finished members measuring 10 mm × 10 mm × 0.56 mm (length × width × thickness). The surface roughness Ra was measured and was 0.03 to 0.05 μm.

[0073] When the magnetostriction constant of 10 pieces with a #1000 grinding finish was measured, the average value was 300 ppm, which was equivalent to the average value of 300 ppm for the magnetostriction constant of 10 pieces with a mirror polishing finish machined from the same area. The manufacturing conditions and evaluation results are shown in Table 1.

[0074] [Example 5] Ten pieces were prepared from the remaining 10 mm×10 mm×1 mm wire saw finished pieces produced in Example 1.

[0075] A #200 grinding wheel was set on a surface grinder, and 10 wire saw finished parts were ground by 100μm on each side to produce #200 ground finished parts of 10mm x 10mm x 0.8mm (length x width x thickness). The surface roughness of this was measured. The surface roughness Ra was 0.3 to 0.6μm.

[0076] When the magnetostriction constant of 10 #200 ground finished parts was measured, the average value was 299 ppm, which was equivalent to the average magnetostriction constant of 10 mirror-polished finished parts machined from the same area, which was 300 ppm. The manufacturing conditions and evaluation results are shown in Table 1.

[0077] [Example 6] Ten pieces were prepared from the remaining 10 mm×10 mm×1 mm wire saw finished pieces produced in Example 1.

[0078] A #100 grinding wheel was set on a surface grinder, and 10 wire saw finished pieces were ground by 100μm on each side to produce #100 ground finished pieces measuring 10mm x 10mm x 0.8mm (length x width x thickness). The surface roughness of these pieces was measured. The surface roughness Ra was 1.8~2.1μm.

[0079] When the magnetostriction constant of 10 #100 ground finished parts was measured, the average value was 285 ppm, which is lower than the average value of 300 ppm for the magnetostriction constant of 10 mirror-polished finished parts machined from the same area, but is almost the same. The manufacturing conditions and evaluation results are shown in Table 1.

[0080] [Comparative Example 1] Ten pieces were prepared from the remaining 10 mm×10 mm×1 mm wire saw finished pieces produced in Example 1.

[0081] A #40 grinding wheel was set on a surface grinder, and 10 wire saw finished parts were ground by 100μm on each side to produce #40 ground finished parts of 10mm x 10mm x 0.8mm (length x width x thickness). The surface roughness of this was measured. The surface roughness Ra was 2.8~4.1μm.

[0082] When the magnetostriction constant of 10 #40 ground finished parts was measured, the average value was 234 ppm, which was significantly lower than the average value of 300 ppm for 10 mirror-polished finished parts machined from the same area. The manufacturing conditions and evaluation results are shown in Table 1.

[0083] [Reference example] Ten pieces were prepared from the remaining 10 mm×10 mm×1 mm wire saw finished pieces produced in Example 1.

[0084] Next, the front and back surfaces of the wire saw finished parts were subjected to surface grinding to adjust the thickness of the parts. Next, the front and back surfaces of the obtained thin plate parts were subjected to mirror finishing to obtain mirror polished parts of 10 mm x 10 mm x 0.5 mm (length x width x thickness). The average magnetostriction constant of 10 mirror polished parts was 300 ppm. The manufacturing conditions and evaluation results are shown in Table 1.

[0085] [Table 1]

[0086] From Examples 1 to 5, it can be seen that the magnetostriction constant can be evaluated without double-sided polishing because the magnetostriction constant is equivalent to that of the double-sided polishing finish even with wire saw finishing or #100 to #1000 grinding finishing. It was confirmed that the surface roughness Ra is in the range of 0.03 to 0.6 μm with wire saw finishing or #100 to #1000 grinding finishing.

[0087] The magnetostriction constant decreased slightly with #100 grinding, and the processing time was longer with #1000, so it was confirmed that wire saw finishing or #200~#600 grinding finishing is more desirable for measuring the magnetostriction constant with high accuracy.

[0088] [summary] From the results of Examples 1 to 5 and Reference Example, it can be seen that a rough surface finish with a surface roughness of Ra 0.1 μm or less results in a magnetostriction constant equivalent to that of a double-sided polished finish. Also, from the results of Examples 1 to 6, it can be seen that a surface roughness of Ra 2.4 or less results in a high magnetostriction constant.

[0089] The technical scope of the present invention is not limited to the aspects described in the above-mentioned embodiments. One or more of the requirements described in the above-mentioned embodiments may be omitted. The requirements described in the above-mentioned embodiments may be combined as appropriate. In addition, to the extent permitted by law, the disclosures of all documents cited in the above-mentioned embodiments are incorporated by reference and made part of the description in this text. [Explanation of symbols]

[0090] 1: Magnetostrictive material 3: Surface 4: Back side 5,6: Side

Claims

1. A magnetostrictive member made of a single crystal of an iron-based alloy having magnetostrictive properties, At least one surface is a non-mirror-polished surface having a surface roughness Ra of 0.03 μm or more and 2.4 μm or less; The magnetostrictive member has a magnetostriction constant of 250 ppm or more. Magnetostrictive material.

2. The magnetostrictive member is plate-shaped, 2. The magnetostrictive member according to claim 1, wherein the front and back surfaces are non-mirror-polished surfaces and have a surface roughness Ra of 0.03 μm or more and 2.4 μm or less.

3. 3. The magnetostrictive member according to claim 1, wherein the surface having a surface roughness Ra of 0.03 μm or more and 2.4 μm or less is a ground surface.

4. A method for manufacturing a magnetostrictive member made of a single crystal of an iron-based alloy having magnetostrictive properties, comprising: A method for producing a magnetostrictive member, comprising: surface-processing at least one surface to a non-mirror-polished surface with a surface roughness Ra of 0.03 μm or more and 2.4 μm or less to obtain a magnetostrictive member having a magnetostriction constant of 250 ppm or more.

5. The method for manufacturing a magnetostrictive member according to claim 4 , wherein the surface processing is a grinding process.

6. 6. The method for producing a magnetostrictive member according to claim 4, wherein the surface treatment is a grinding process using a grindstone having a grit size of #100 or more and #1000 or less.

Citation Information

Patent Citations

  • JP1973095108A

  • Strain measuring method

    JP1988281032A

  • Growing device for single crystal of fe-si-al-based alloy

    JP1992108699A

  • Stress detecting element

    JP1998038710A

  • Torque sensor and its manufacturing method

    JP2002250662A